Flow velocity measurement in haemodialysis access using 4D MRI - Downs, Jennifer (Department of Surgery, 2017)
Treatment of renal failure while awaiting transplant requires vascular access, which comes with both complications and failure rates. In order to improve this, information about the AVF or AVG itself, as well as the haemodynamics is required. This data will then be used for computer modelling techniques and computational flow dynamics. Previously, the required imaging was provided by contrasted MRI, contraindicated in renal failure. Haemodynamic data was prvided by, amongst other things, duplex Doppler. New MRI software that provides imaging data as well as haemodynamic information without using contrast could be used to provide new high-quality data for modelling. Methods: This was a prospective pilot study. Six control cases (with no history of vascular illness or surgery of any kind to the right upper arm), as well as three grafts and five fistulae underwent phase contrast MR angiography of the right upper arm with a Siemens Magnetom Symphony 1.5T MRI Scanner. Images were then processed using Supertool in Matlab, and flow velocities at predetermined points on the brachial artery and cephalic vein, graft and fistula were calculated. Results: Velocities ranged from 5.8 cm/sec in a volunteer's brachial artery to 85.5 cm/sec in an arteriovenous fistula patient's brachial artery. Flow volumes in the cephalic vein or access varied from 6.9 ml/min. in a volunteer and up to 4398.1 ml/min. in an arteriovenous fistula. Graphical representations show marked haemodynamic changes throughout the imaged vessels. Conclusion: This technique provides good imaging and quantitative data about small vessel haemodynamics.